Paleometric approaches reveal striking differences in the insect fossilization of two Mesozoic Konservat-Lagerstätten - Storari, Arianny P.; Osés, Gabriel L.; Staniczek, Arnold H.; Rizzutto, Marcia; Loeffler, Ronny; Rodrigues, Taissa (Frontiers in Ecology and Evolution, 2024)
The Crato Formation (Lower Cretaceous, Brazil) is a Konservat-Lagerstätte preserving a great number of exceptionally well-preserved insects. Here, we sought to explore the preservational modes of two abundant aquatic and terrestrial groups of this unit, mayflies and crickets. To better understand how exceptional is their preservation, we also present detailed data on the modes of preservation of mayflies from the renowned Solnhofen limestones (Upper Jurassic, Germany). For the Crato Formation, out of 234 fossil mayflies and crickets, ten specimens were additionally analyzed using scanning electron microscopy coupled to energy dispersive X-ray spectroscopy (SEM-EDS), energy and micro-energy dispersive X-ray fluorescence (EDXRF and µEDXRF), and µRaman spectroscopy. For the Solnhofen limestones, 85 adult mayflies were analyzed, and five of them were subjected to SEM-EDS and µEDXRF analyses. The Crato specimens preserve several external and internal microfeatures. The areas with the highest fidelity of preservation are characterized by smaller and more closely-packed crystals when compared to less-preserved parts. We also recovered microscopic features that suggest the presence of microbial mats during the fossilization process. All the analyzed Crato specimens are preserved by replacement of tissues with iron oxides after pyritization. Sulfur occurs scattered in some regions of the crickets, but is associated with low iron counts, which may indicate the presence of sulfates post-dating pyrite oxidation. Additionally, the orthopterans have calcium phosphate preserving some of their structures. Differing from Crato insects, Solnhofen mayflies are overall poorly preserved as mere imprints, and their micron-scale morphology is obliterated by coarse mineral growth, whereas tissues are obliterated by calcite crystals alone or in combination with globular material. There is an elevated concentration of Si, K, Ca, Ti, Mn, and Fe in comparison to the host rock, which may be related to a yet unknown mineral phase(s). Although the paleoenvironments of the Crato Formation and the Solnhofen limestones are different, there are similarities in the style of preservation of their vertebrates and in some of their paleoenvironmental conditions such as anoxic hypersaline bottom waters and deposition of laminated limestones. However, the same does not apply to the preservation of insects, specifically mayflies, which are poorly preserved in the Solnhofen limestones.